Método gravimétrico para determinar la longitud de fibra en mechas de lana de ovejas - Alvarez V, Victor Hugo; F Atkinson, Glen (Revista Ceres, 2025)
A gravimetric method to determine the average length and the percentages of different lengths of fibers in stretched out hank wool of sheeps is presented.